The Difference in Perception between Nursing Students and Clinical Teachers of the Characteristics of Clinical Teachers - Yulia M. K. Letor; Melianus M. Taebenu; Herliana M. A. Djogo (JENDELA NURSING JOURNAL, 2022)
Background: clinical teachers play essential roles in nursing education. They link knowledge gained by students in classrooms into clinical settings. This makes the characteristics of clinical teachers need to be effective to facilitate nursing students in clinical settings.Purpose: to compare the perception of nursing students and clinical teachers of the characteristics of clinical teachers at the Institute of Health Sciences of Citra Husada Mandiri Kupang, Indonesia.Methods: a cross-sectional design. Data was collected from third and fourth-year undergraduate nursing students (n= 201) and clinical teachers (n= 13). Two statistical tools were used to analyze and interpret the data: Weighted Mean and T-test.Results: there was a statistical difference in the perception of nursing students and clinical teachers of the characteristics of clinical teachers in three subsets - professional competence, relationship with students, and personal attributes.Conclusion: a gap in perceptions regarding the characteristics of the clinical teachers exists between both groups of participants. It is essential for the Institute to bridge the gap or to ensure that the students perceive their clinical teachers better.